The Vocational Counseling of Adults and Young Adults. A Philosophy of Adult Counseling - Thoroman, E. C. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
A number of factors indicate an increased need for vocational counseling services for adults, chief among them being the economic factors of increased material needs, inflation, and technological change; the social factors of unemployment or underemployment; and the increase of women in the job market. The conventional pattern of testing, profile interpretation, prescription, and placement is not adequate to the task of helping adults reshape their occupational outlook. A philosophy centered on the individual, dynamic self-concept of the client is more contemporary. The place of the counselor within this philosophy is to be versatile, well informed, and flexible in helping clients to shape their goals. These goals must be: (1) immediate in time, (2) clearly defined, (3) intellectually attainable, and (4) contributory to the client's ego satisfaction. (BP)
Availability: The complete book is available from Houghton Mifflin Company, 110 Tremont Street, Boston, Massachusetts 02107 ($4.50).
ERIC Note: This abstract encompasses only Chapter 1, A Philosophy of Adult Counseling, pages 1-16.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Career Counseling; Educational Counseling; Self Concept; Adult Counseling; Counseling Objectives; Counseling Theories; Counselor Attitudes